2007
DOI: 10.13182/fst07-a1324
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Induced Instability of Diocotron Modes in Electron Plasmas Modelling Curvature-Driven Flute Modes

Abstract: We study ion-induced instability of flute-like (k z º 0) diocotron modes in pure electron plasmas confined in a cylindrical Penning-Malmberg trap. In the absence of positive ion contamination, the low m θ diocotron modes are either neutrally stable (for m θ = 1) or weakly damped (for m θ = 2,3…) by Landau resonance on electrons corotating with the diocotron waves. By adding a small fraction (< 1%) of positive ions into a double-well confinement configuration, we observe exponential instability of low m θ dioco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In Penning or Penning double well traps, the ion-resonant mode has a finite growth rate at essentially any neutral pressure, and the mode grows steadily until the plasma disperses [20,25]. In CNT and in full toroidal traps non-neutral plasmas are stable for low ion fractions n i =n e < 0:1 [8,15].…”
mentioning
confidence: 99%
“…In Penning or Penning double well traps, the ion-resonant mode has a finite growth rate at essentially any neutral pressure, and the mode grows steadily until the plasma disperses [20,25]. In CNT and in full toroidal traps non-neutral plasmas are stable for low ion fractions n i =n e < 0:1 [8,15].…”
mentioning
confidence: 99%
“…For many years, it was thought that these instabilities are driven by the different drift rotation frequencies caused by inertial effects (mass difference). However, in past experiments [2,7] we have shown that an ion contamination of pure electron plasmas leads to the ion-induced diocotron (IID) instability, determined by the differences in z-bounce-averaged for electrons and ions with different z-bounce regions (as in "nested" or double-well traps configuration). Quite often, an ion fraction is continuously produced in warm(ish) electron plasma experiments, and special arrangements need to be made to prevent those ions from being trapped.…”
Section: Ion-induced Instability Of Diocotron Modesmentioning
confidence: 99%
“…where (see [2]). Figure 2 shows the measured growth rate of the IID instability as a linear function of the background pressure.…”
Section: Ion-induced Instability Of Diocotron Modesmentioning
confidence: 99%
“…The primary cause for such contamination (either planned or inadvertent) in most electron plasma trap experiments is the process of ionization of the neutral background gas in the trap by the electrons. A brief history of analytical modelling 1,[4][5][6][7][8] , numerical analysis 9 , and experiments [10][11][12][13][14][15][16][17] performed to understand this destabilization process can be found in Sec I of Reference 3 3 . Of the theoretical models for the ion resonance instability, the one developed by Davidson and Uhm 5 aptly describes the collisionless dynamics of the instability in the present set of numerical experiments performed with an initially cold, partially neutralized electron cloud in cylindrical confinement.…”
Section: Introductionmentioning
confidence: 99%